Magnetic field swimmer positioning - Marshall, Joe (IEEE, 2015)
Several projects have tracked the movement of swimmers in pools using body worn inertial measurement units. In swimming, inertial sensing is subject to large amounts of drift and accumulated error which can only be corrected for after a complete length has been swum. In this article, we present a new method for tracking swimmers by detecting variations in the magnetic field caused by the structure of pools. This method is complementary to inertial positioning, as it allows the direct extraction of position without requiring post-processing, and unlike inertial sensing which loses accuracy over time, magnetic field tracking becomes increasingly accurate towards the end of a length.